Pengaruh Model Pembelajaran Kooperatif Terhadap Peningkatan Mutu Hasil Belajar Siswa - Sudarsana, I Ketut (LPM IHDN Denpasar, 2018)
The philosophy of cooperative learning model of Group Investigation is constructivism, which in the learning process is not transferring knowledge from teacher to students, but the students themselves who actively find something and build their own knowledge, not a mechanical process to collect facts. Students are responsible for the learning outcomes. Students make the reasoning of what they learn by means of finding meaning, comparing it with what is already known, and resolving the inequality between what is already known and what is needed in the new experience.